PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP PERINGKAT OBLIGASI - Dewi, Kadek Kristiana; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
The purpose of this study was to determine the effect of corporate governance, profitability, liquidity and solvability on bond rating. The population used in this study is a registered company in Indonesia Stock Exchange 2002-2013 period and the sampling method used is purposive sampling. Samples were obtained as many as 70 company issuing the bond. The data analysis technique used is Ordinal Logistic Regression. The study found that good corporate governance which is proxied by corporate governance perception index, profitability is proxied by Return on Assets and solvency proxied by Cash Flow from Operating / Total Liabilities positive effect on bond ratings, while liquidity by proxy Current Ratio has no effect on bond rating.
Keywords: bond rating, GCG, profitability, liquidity, solvability